2011
DOI: 10.1007/s00784-011-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal inflamed surface area and C-reactive protein as predictors of HbA1c: a study in Indonesia

Abstract: Periodontitis may exert an infectious and inflammatory burden, evidenced by increased C-reactive protein (CRP). This burden may impair blood glucose control (HbA1c). The aim of our study was to analyze whether periodontitis severity as measured with the periodontal inflamed surface area (PISA) and CRP predict HbA1c levels in a group of healthy Indonesians and a group of Indonesians treated for type 2 diabetes mellitus (DM2). A full-mouth periodontal examination, including probing pocket depth, gingival recessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 41 publications
3
41
1
1
Order By: Relevance
“…Besides molecular and cellular specificity in the acute and the chronic setting that can each uniquely contribute in shaping the observed association, it is also possible that local bacterial drive in course of active periodontitis exerts additional immunological and metabolic systemic effects, similar to what described for gut dysbiosis and several systemic diseases (Del Pinto, Ferri, & Cominelli, ; Del Pinto, Wright, Monaco, Pietropaoli, & Ferri, ; Hajishengallis, ; Kourtzelis et al, ; Lamont, Koo, & Hajishengallis, ). Our findings of an association between high/uncontrolled BP and severe scores of periodontal inflammation are in line with previous results (Martin‐Cabezas et al, ; Pietropaoli et al, ) and add information of interest to the sparse previous literature relating PISA to chronic low‐grade inflammatory conditions, particularly diabetes (Nesse et al, ; Susanto et al, ). Specifically, there is evidence that PISA is a predictor of impaired glycaemic control together with CRP and better than other periodontal parameters alone (PPD, CAL, and BoP), supporting the contribution of periodontal inflammation, expressed as PISA, to the systemic inflammatory burden denoted by increased levels of CRP (Susanto et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Besides molecular and cellular specificity in the acute and the chronic setting that can each uniquely contribute in shaping the observed association, it is also possible that local bacterial drive in course of active periodontitis exerts additional immunological and metabolic systemic effects, similar to what described for gut dysbiosis and several systemic diseases (Del Pinto, Ferri, & Cominelli, ; Del Pinto, Wright, Monaco, Pietropaoli, & Ferri, ; Hajishengallis, ; Kourtzelis et al, ; Lamont, Koo, & Hajishengallis, ). Our findings of an association between high/uncontrolled BP and severe scores of periodontal inflammation are in line with previous results (Martin‐Cabezas et al, ; Pietropaoli et al, ) and add information of interest to the sparse previous literature relating PISA to chronic low‐grade inflammatory conditions, particularly diabetes (Nesse et al, ; Susanto et al, ). Specifically, there is evidence that PISA is a predictor of impaired glycaemic control together with CRP and better than other periodontal parameters alone (PPD, CAL, and BoP), supporting the contribution of periodontal inflammation, expressed as PISA, to the systemic inflammatory burden denoted by increased levels of CRP (Susanto et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…For CAL ≥7 mm, only DM2 remained a significant factor. Recently, Susanto et al 48 found similar results. In their study evaluating the role of DM2 on periodontitis in the Indonesian population, age was an additional predictor of periodontitis severity (along with DM2), when considering CAL levels and not for PD values.…”
Section: Discussionmentioning
confidence: 59%
“…In their study evaluating the role of DM2 on periodontitis in the Indonesian population, age was an additional predictor of periodontitis severity (along with DM2), when considering CAL levels and not for PD values. As highlighted by the authors, this result could be expected because CAL reflects the accumulation of damage sustained by the periodontium over time 48 . It assumes that with increased age, CAL increases accordingly.…”
Section: Discussionmentioning
confidence: 67%
“…The number of teeth (NT) was also recorded and patients having ≥8 teeth were included to the study. 14 Determination of the systemic inflammatory burden The classification reported by Hujoel 11 measures the total attachment loss surface area. This classification was modified to obtain a classification system regarding the periodontally inflamed surface area by Nesse 12 The modified version of the classification 12 was used to calculate the periodontally inflamed surface area (PISA) and periodontally epithelial surface area (PESA) using PD, CAL and BOP.…”
Section: Clinical Periodontal Parametersmentioning
confidence: 99%
“…11,12 A measurement and classification system developed by Hujoel 11 and modified by Nesse 12 was used for related periodontitis with systemic diseases in recent years. [12][13][14] From this point of view, this study was aimed to test the hypothesis whether periodontitis related systemic inflammatory burden, measured by a scale using clinical periodontal parameters, have a correlation with the future cardiovascular events using Framingham Risk Score (FRS). Patients who undergo for coronary angiography with suspicion of CAD between the ages 30 and 75 were included.…”
Section: Introductionmentioning
confidence: 99%